Application Design: Integration of Qris E-Wallet Cryptocurrency Using Prototype Method: Perancangan Aplikasi : Integrasi Qris E-Wallet Cryptocurrency Dengan Metode Prototype - Almanfaluti, Istian Kriya; Putri , Niken Amelia; Navaro , Muhammad Saddam (Universitas Muhammadiyah Sidoarjo, 2024)
This research endeavors to contribute to the rapidly evolving landscape of technology-driven payment systems, with a focus on Indonesia. The primary objective is to design and develop a mobile application for a cryptocurrency digital wallet integrated with Quick Response Code Indonesian Standard (QRIS). The methodology involves utilizing Webservice for seamless implementation and Android Studio Framework for efficient mobile application development. The results showcase the successful creation of a mobile application that enables cryptocurrency owners to convert virtual assets into Indonesian Rupiah for various transactions, including purchasing mobile credits, electricity tokens, travel tickets, and other payments. The evaluation underscores the feasibility and practicality of the proposed solution, emphasizing the potential for increased ease, speed, and efficiency in transaction processing. This research opens avenues for further exploration and implementation of cryptocurrency-based payment systems, addressing the evolving needs of the digital economy in Indonesia and potentially serving as a model for global applications.Highlights : Seamless Implementation: The research successfully employs Webservice for the integration of a cryptocurrency digital wallet with QRIS, ensuring a smooth and efficient transaction process. Android Studio Framework: The use of the Android Studio Framework demonstrates the applicability and versatility of established tools in developing a robust and user-friendly mobile application for cryptocurrency transactions. Efficiency in Digital Transactions: The designed mobile application enables cryptocurrency owners to convert virtual assets to Indonesian Rupiah, enhancing transaction speed, ease, and overall efficiency in various financial interactionKeywords: Cryptocurrency, E-Wallet, QRIS Integration, Mobile Application, Digital Transactions. Keywords : Cryptocurrency, E-Wallet, QRIS Integration, Mobile Application, Digital Transactions.